Gel immersion endoscopic mucosal resection for early gastric neoplasms: a multicenter case series study - Kimura, Hidenori; Yamamoto, Yoichi; Yabuuchi, Yohei; Shigeta, Kohei; Yoshida, Masao; Nagao, Soichiro; Noguchi, Akito; Morita, Yukihiro; Shintani, Shuhei; Inatomi, Osamu; Ono, Hiroyuki; Andoh, Akira (Endoscopy International Open, 2024)
Several cases have been reported that suggest the efficacy of gel immersion endoscopic mucosal resection (GI-EMR) for gastric neoplasms. However, no study has evaluated treatment outcomes of GI-EMR for gastric neoplasms. This study aimed to investigate the efficacy and safety of GI-EMR for early gastric neoplasms. Nine patients (17 lesions) undergoing gastric GI-EMR were included, with a median lesion size of 10 mm (interquartile range [IQR] 5–13 mm). All lesions were protruding or flat elevated. The median procedure time was 3 minutes (IQR 2–5) and en bloc resection was achieved in all cases. Among 15 neoplastic lesions, the R0 resection rate was 86.7% (13/15 lesions). Adverse events included immediate bleeding requiring hemostasis in two cases, which was controlled endoscopically. No delayed bleeding or perforation occurred. In conclusion, GI-EMR may be a safe and effective treatment for early, small gastric neoplasms. However, due to the small sample in the present study, further investigation is required regarding the indication for this technique.
Keywords: Endoscopic resection (ESD, EMRc, ...); Endoscopy Upper GI Tract; Precancerous conditions & cancerous lesions (displasia and cancer) stomach